An Unusual Case of Bilateral Granulomatous Mastitis. (23rd May 2013) - Pistolese, C. A.; Di Trapano, R.; Girardi, V.; Costanzo, E.; Di Poce, I.; Simonetti, G.
Abstract : Idiopathic granulomatous mastitis (IGM) is an uncommon benign disorder of the breast. At clinical examination, IGM is characterized by an inflammatory process of the breast, usually unilateral. Possible clinical findings are palpable mass with erythematous skin, pain, sterile abscesses, fistula and nipple retraction. Mammography and ultrasound findings are not specific for IGM. Magnetic resonance imaging (MRI) is a useful tool for the differential diagnosis; it is also necessary to delineate the exact extension of the disease and to plan the correct treatment. Final diagnosis is histological. We described an unusual case of IGM with bilateral involvement in a patient with history of pacemaker implantation and IGM typical clinical symptoms. Mammography, ultrasound, and MRI examinations were performed to identify the inflammatory disorder and to plan the correct therapy. Imaging features were correlated with final histological diagnosis of IGM.